Coriolus versicolor alleviates diabetic cardiomyopathy by inhibiting cardiac fibrosis and NLRP3 inflammasome activation. (23rd July 2019) - Wang, Yueqiu; Li, Hui; Li, Yang; Zhao, Yihan; Xiong, Fangfei; Liu, Yining; Xue, Hongru; Yang, Zhenyu; Ni, Sha; Sahil, Abbas; Che, Hui; Wang, Lihong
Abstract : Coriolus versicolor (CV) is a traditional medicine and food mushroom. Our previous study demonstrated that CV extract exhibited anti‐hyperglycemia and anti‐insulin resistance effects. However, the effect of CV on cardiac function in diabetic cardiomyopathy (DCM) remains unclear. Therefore, we aimed to investigate the effect of CV on cardiac function in diabetes mellitus (DM) rats. We found that the cardiac dysfunction of DM rats was markedly improved by CV extract treatment. CV extract administration significantly attenuated cardiac fibrosis in DM rats, which was accompanied by suppressed transforming growth factor beta 1 (TGF‐β1)/Smad signaling as indicated by decreased levels of TGF‐β1, p‐Smad2, and p‐Smad3 and increased Smad7 expression. Moreover, CV extract treatment significantly alleviated cardiac inflammation as shown by decreased levels of NLRP3 receptor, cleaved caspase‐1, IL‐1β, and IL‐18 in DM rats at least partly due to the inhibition of the NF‐κB. In addition, high‐glucose treatment induced cardiac fibrosis and increased cardiac inflammation in cardiac fibroblast cells, but these effects were ameliorated by CV extract treatment. Therefore, we conclude that the protective effect of CV on DCM is associated with the suppression of TGF‐β1/Smad signaling and attenuation of NLRP3 inflammasome activation, suggesting that CV extract may be a potential therapeutic agent for DCM.